2013
DOI: 10.4271/2013-01-0462
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Drag Reduction on a Simple Car-Like Shape with Rear Upper Body Taper

Abstract: Various techniques to reduce the aerodynamic drag of bluff bodies through the mechanism of base pressure recovery have been investigated. These include, for example, boat-tailing, base cavities and base bleed. In this study a simple body representing a car shape is modified to include tapering of the rear upper body on both roof and sides. The effects of taper angle and taper length on drag and lift characteristics are investigated. It is shown that a significant drag reduction can be obtained with moderate ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…The downwash created by the top slanted surface, indeed, leads to a shift of the region with the highest values of C P rms (associated with bi-stability) towards the bottom trailing edge, with the appearance of three zones of low unsteadiness close to the top edge of the base. In particular, the first two regions are placed close to the tips of the taper, in the same zones where the longitudinal trailing vortices created by the slant (as already shown by the PIV results obtained by Howell et al in [28] for a similar configuration) are expected to interact with the near wake recirculation. The third region of low unsteadiness, is positioned close to the middle of the taper trailing edge, where the amount of flow deflected by the taper into the model wake reaches its maximum.…”
Section: Top Tapermentioning
confidence: 52%
“…The downwash created by the top slanted surface, indeed, leads to a shift of the region with the highest values of C P rms (associated with bi-stability) towards the bottom trailing edge, with the appearance of three zones of low unsteadiness close to the top edge of the base. In particular, the first two regions are placed close to the tips of the taper, in the same zones where the longitudinal trailing vortices created by the slant (as already shown by the PIV results obtained by Howell et al in [28] for a similar configuration) are expected to interact with the near wake recirculation. The third region of low unsteadiness, is positioned close to the middle of the taper trailing edge, where the amount of flow deflected by the taper into the model wake reaches its maximum.…”
Section: Top Tapermentioning
confidence: 52%
“…Howell et al [25] showed, using the Windsor geometry but as here applying the tapering only to the upper half of the body, that the introduction of a shoulder into the geometry leads to the formation of a vortex which, in turn, generates downwash. This mechanism is likely to be present for the SUV with the streamwise vortices from the shoulder producing a downwash and an inwash resulting in a recirculation in the upper region of the base (low pressure and low fluctuations) and a downwash dominated wake.…”
Section: Side Tapersmentioning
confidence: 99%
“…The details of this model have been well documented previously (see, for example [7], [17] and [18]). The model is 1.044m long, 0.389m wide and 0.289m high.…”
Section: Physical Modelmentioning
confidence: 87%